A aprendizagem da docência: narrativas autobiográficas de professoras de crianças em escolas no campo do município de Ipiranga/PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
This research focuses on the teaching learning process of preschool teachers in the municipality of Ipiranga-Paraná/PR, Brazil. The central question is: How does the teaching learning process of teachers working with children unfold in schools in the rural area of Ipiranga/PR? In order to address this question, the general objective is to comprehend the aspects shaping the teaching learning process of preschool teachers in schools located in the rural area of Ipiranga/PR. The specific objectives are: to characterize the aspects related to the formative journey of teachers in rural schools of Ipiranga engaged in Early Childhood Education; to identify the characteristics of the work of teachers in rural schools in Early Childhood Education in the municipality; and to understand the challenges faced by teachers in the municipality of Ipiranga in their work with Early Childhood Education. This qualitative research employed a bibliographical study and the production and analysis of data from autobiographical narratives. The study focused on six rural schools in the municipality of Ipiranga/PR. Data generation instruments included a questionnaire administered via Google Forms, addressing the profiles of the 12 preschool teachers in rural schools. Of these, three teachers participated in the second phase, which involved producing autobiographical narratives about their teaching learning trajectories. Finally, a roundtable discussion and a narrative interview with the participants were proposed. The analyses were informed by scholars such as Mizukami (2005, 2010), Freire (2023), Arroyo (1999, 2023), Caldart (2002, 2003, 2012), Fernandes and Molina (2004), Souza (2004, 2006, 2008, 2016, 2020, 2022), among others. The study concludes that the teaching learning process of preschool teachers working with young children in schools in the rural area of Ipiranga/PR is shaped by diverse familial, social, and formative relationships, such as marriage, the arrival of children, life experiences emphasizing acts like caring for younger siblings, assisting parents, opportunities encountered throughout life, and challenges faced. In terms of formative and professional aspects, the teachers highlight the importance of support from more experienced colleagues, finding care, dedication, and support in the school environment, as well as in initial and ongoing training, reflections, and decision-making in teaching work. In this way, the study contributes to social reflections and analyses regarding how Early Childhood Education teachers learn to be educators, aiming for their social and professional recognition within and beyond school spaces.
Keywords: Aprendizagem da Docência; Educação Infantil; Educação do Campo; Prática Pedagógica; Teaching Learning Process; Early Childhood Education; Rural Education; Pedagogical Practice; CNPQ::CIENCIAS HUMANAS::EDUCACAO